Investigation of cyano-bridged coordination nanoparticles Gd3+/[Fe(CN)6]3−/d-mannitol as T1-weighted MRI contrast agents. Issue 28 (13th May 2015) - Perrier, M.; Gallud, A.; Ayadi, A.; Kennouche, S.; Porredon, C.; Gary-Bobo, M.; Larionova, J.; Goze-Bac, Ch.; Zanca, M.; Garcia, M.; Basile, I.; Long, J.; et al.
Abstract : Ultra small Gd 3+ /[Fe(CN)6 ] 3− nanoparticles are investigated in vivo as contrast agents for Magnetic Resonance Imaging. Abstract : Cyano-bridged Gd 3+ /[Fe(CN)6 ] 3− coordination polymer nanoparticles of 3–4 nm stabilized withd -mannitol presenting a high r 1 relaxivity value of 11.4 mM −1 s −1 were investigated in vivo as contrast agents (CA) for Magnetic Resonance Imaging (MRI). They allow an increase of the MR image contrast and can act as an efficient intravascular T 1 CA with a relatively long blood-circulation lifetime (60 min) without specific toxicity.